Documenting the Use of Computers in Swedish Health Care up to 1980 - Peterson, H. E.; Lundin, P. (Yearbook of Medical Informatics, 2011)
This paper describes a documentation project to create, collect and preserve previously unavailable sources on informatics in Sweden (including health care as one of 16 subgroups), and mak- ing them available on the Web. Time was critical as the personal docu- mentation and artifacts of early pioneers could be irretrievablylost. The criteria for participation were that a person had developed a system in a clinical environment which was used by others prior to 1980.Participants were interviewed and asked for early docu- mentation such as notes, minutes from meetings, drawings, test results and early models – together with related artifacts. The ap- proach included traditional oral history interviews, collection of au- tobiographies and new self-structuring and time saving methods, such as witness seminars and an Internet-based repository of their recollections (the Writers’ Web).The combination of methods obtained new information on system errors, and challenges in reaching the goals due partly to inadequacies of the early technology, and partly to the insufficient understanding of the complexity of the many problems which needed to be solved before a useful electronic patient record could be realized. A very important result was the development of a method to collect information in an easier, faster and much less expensive way than using the traditional scientific method, and still reach results that are qualitative and quantitative for the purpose of documenting the early period of computer-based health care technology. The wit- ness seminars and the Writers’ Web yielded especially large amounts of hitherto-unknown information. With all material in one database available to everyone on the Web, it is accessed very frequently - es- pecially by students, researchers, journalists and teachers.Study of the materials explains and clarifies the reasons behind the delays and difficulties that have been encountered in de- veloping electronic patient records, as described in an article [3] published in the IMIA Yearbook 2006.
Keywords: Swedish medical informatics; historical documentation; clinical informatics systems; electronic patient records; methodology of in- formation gathering; Writers’ Web